2018
DOI: 10.1002/acp.3428
|View full text |Cite
|
Sign up to set email alerts
|

Reduced autobiographical memory specificity as a mediating factor between general anxiety symptoms and performance on problem‐solving tasks

Abstract: This study sought to further explain the association between general anxiety symptoms and impaired problem-solving by testing whether this occurs, in part, through a reduced ability to retrieve event-level, specific autobiographical memory (AM).Participants (N = 301; M age = 28.2 SD = 7.7, 55.8% female) completed assessments of the retrieval of specific AM, anxiety symptoms, depressive symptoms, and rumination. They then completed the Means-End Problem Solving Task, which assessed their ability to produce rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
11
1
Order By: Relevance
“…It is of note that, among these included studies, the within-group effect size for the Anxiety Disorder diagnostic category was not statistically significant. This finding contrasts with studies in community samples that indicate that trait and state levels of general anxiety are correlated with rAMS (Hallford, Noory, et al, 2018; Hallford & Mellor, 2017; Hallford et al, 2019). Our finding may be explained by the small sample size and heterogeneity between diagnoses included within this category.…”
Section: Discussioncontrasting
confidence: 99%
“…It is of note that, among these included studies, the within-group effect size for the Anxiety Disorder diagnostic category was not statistically significant. This finding contrasts with studies in community samples that indicate that trait and state levels of general anxiety are correlated with rAMS (Hallford, Noory, et al, 2018; Hallford & Mellor, 2017; Hallford et al, 2019). Our finding may be explained by the small sample size and heterogeneity between diagnoses included within this category.…”
Section: Discussioncontrasting
confidence: 99%
“…Lastly, 10% of MEPS solutions were coded by a second rater for inter-rater reliability assessment, consistent with past studies (e.g. Glazebrook et al, 2015;Hallford et al, 2018). Future research should consider estimating reliability using a larger number of participants for greater precision.…”
Section: And Conclusionmentioning
confidence: 86%
“…Many studies have attempted to clarify whether increased OGM was in relation to anxiety disorder, however, the findings were less consistent [22,29,30]. Studies on general anxiety disorder (GAD) indicated that individuals with GAD displayed difficulty in retrieving specific autobiographical memories [29][30][31].…”
Section: Overgeneral Autobiographical Memory (Ogm)mentioning
confidence: 99%
“…Many studies have attempted to clarify whether increased OGM was in relation to anxiety disorder, however, the findings were less consistent [22,29,30]. Studies on general anxiety disorder (GAD) indicated that individuals with GAD displayed difficulty in retrieving specific autobiographical memories [29][30][31]. In contrast, some studies on social anxiety [32][33][34] and specific phobias [35] have demonstrated that there is no notable relationship between anxiety and specific autobiographical memories.…”
Section: Overgeneral Autobiographical Memory (Ogm)mentioning
confidence: 99%